Sekundarna gospodarska središča v Ljubljani - Bole, David (Urbani izziv, 2010)
This paper presents secondary business districts in Ljubljana according to theconditions in the 2008 proposal of the City of Ljubljana spatial plan. The introduction first clarifies the term "secondary business district" and continues by presenting the basic typology of secondary business districts, which is based on a historical approach and represents an inventory of these districts in Ljubljana. Selected features of these districts are presented, especially from the business viewpoint. The structure of companies, the time of their establishment, capital ownership and size are presented in greater detail. The second part analyses the draft spatial plan in order to determine the future changes in secondary business districts, their creation and disappearance. Simple criteria are used to critically assess the City of Ljubljana draft spatial plan and identify the six most critical secondary business districts that deviate significantly from these criteria.
Keywords: ekonomska geografija; Ljubljana; prostorsko planiranje; spatial planning; urbana geografija; urbanistični načrti